Strategies to Ensure Accurate Calculation of Parameters of the VO2 Response Profile During Heavy Intensity Cycle Ergometer Exercise - Hill, David Wilfred (International Journal of Sport Studies for Health, 2019)
Background: The parameters of the VO2 response profile are obtained by fitting breath-by-breath VO2 data from an exercise test to an appropriate mathematical model. Several strategies have been recommended to ensure, or at least improve, the accuracy of the values. Objectives: The purpose of this study was to evaluate two strategies to enhance the accuracy of parameter estimates that describe the two-component VO2 response during heavy intensity exercise. The first was to use data from a number of tests rather than just one. The second was to ‘smooth’ the data, using three-breath, five-breath, or seven-breath rolling averages of the breath-by-breath VO2 data prior to fitting the data to the two-component model. Methods: Twenty participants (eight women and twelve men) performed six 6-min heavy-intensity (midway between the ventilatory threshold and VO2max) cycle ergometer tests. Breath-by-breath data and smoothed data from each test were fit to a two-component model. The parameter estimates from the first test, and the average of the values from the first two, first three, first four, first five, and all six tests were compared against the criterion value, which was the average of all six values obtained using five-breath averages. Results: Modeling five-breath averages of data from the first test generated values for the parameters that were closely related to the criterion values. Modeling data from two or three tests improved the accuracy slightly, but improvements were small, and negligible when more than three tests were included. Conclusions: Depending upon the accuracy required, that is depending upon how close each and every participant’s value must be to his or her ‘true’ value, smoothed data from one or two tests is sufficient to calculate the values that describe the two-parameter VO2 response profile in heavy intensity cycling exercise.